Gender styles and tyranny of binarism: Why we need the concept of genderlect (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
In this article the question of the relationship between gender and lan- guage is analyzed, specifically the concept of genderlect, arguing that it can help us to get closer to understanding how feminine and masculine identities are constructed. What is it we call feminine, and what masculine? In everyday life every- one at some point has described someone’s bodily action or speech act as feminine or masculine, but neither in the social sciences nor in dis- course analysis have these styles been characterized. The exploration of genderlects will allow us to discover what in a specific cultural con- text is considered masculine and feminine, and how these stereotypes are used to sanction those acts (and people) who do not meet cultural expectations. The work aims to review a number of basic definitions to define the scope of the concept of genderlect, based on some important mile- stones in feminist literature and in studies about gender and language, and finally to examine the importance of this concept for gender studies.
Keywords: Genderlect; feminine; masculin; feminist literature.